18F FDG PET/CT Findings in a Patient with Sarcoidosis: A Case Report - Akhter, Papia; Mutsuddy, Pupree; Mandal, Tapati; Sajjad Al Mishal, Mohammad; Rahman, SM Arifur; Siddique, Md Abu Bakker; Begum, Shamim M F (Bangladesh Journal of Nuclear Medicine, 2024)
Sarcoidosis is a multisystem disease characterized by the formation of noncaseating granulomas that can affect any site in the body with extremely variable clinical course. Fluorine -18 Fluorodeoxyglucose positron emission computed tomography (18F FDG PET/CT) is a useful technique for detecting active inflammatory sites in patients with sarcoidosis thus diagnosis, monitoring response and predicting prognosis. Here we present the case of a 44-year-old lady with sarcoidosis having hepatic involvement detected by 18F FDG PET/CT scan. This patient was presented with increasing complaints of low-grade fever, weight loss and generalized weakness for two years who was found to have a hilar lymphadenopathy in chest X-ray and chest CT scan. 18F FDG PET/CT scan performed to see the extent of disease and revealed multiple hypermetabolic mediastinal and abdominal lymph nodes. There was also heterogenous intense FDG uptake (SUVmax:9.6) in liver without definite change on CT likely due to sarcoidosis involvement in the liver. Later on, hepatic biopsy confirmed the diagnosis of hepatic sarcoidosis. Bangladesh J. Nuclear Med. 27(1): 107-111, 2024